The Impact of Digital Trust on Firm Value and Governance - Kluiters, Leon; Tyll, Ladislav; Srivastava, Mohit; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
This study investigates the main effects of digital trust on firm value. This study has developed a novel method to empirically measure digital trust by combining multiple variables to create a combined digital trust score. Variables include security and privacy scores, security rankings and data breaches. The research evaluates all listed US firms over the period of 2011 to 2016. Significant evidence is found that increasing digital trust leads to an increase in firm value.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses